The Civil War : "A house divided" - Kent, Zachary (Berkeley Heights, N.J. : Enslow, 1994)
Recounts through text, photographs, illustrations, and maps the campaigns and battles of the Civil War as recalled by soldiers and citizens of the period.
Storm over Fort Sumter -- War in the West -- War in the East -- Behind the lines -- When this cruel war is over -- Collapse of the Confederacy.
Includes a chronology of the events and battles of the war.
Includes bibliographical references (p. 126) and index.
Book Links (A.L.A.).
School Library Journal.
Wilson's Junior High School.
6.4
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile literature; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1861-1865, Civil War